Análise experimental do comportamento e durabilidade de vigas de concreto armadas à flexão com barras de GFRP submetidas à ação de solução salina - Mazzú, Amanda Duarte Escobal (Universidade Federal de São Carlos, 2025)
Considering the problems caused by corrosion of steel reinforcement in reinforced concrete structures, often associated with the action of chloride ions, Fiber Reinforced Polymers (FRP), which are non-metallic materials with high mechanical strength, magnetically inert and with good corrosion resistance, have shown to be a viable alternative. However, this material is also subject to degradation, and its relatively recent application in concrete structures implies a lack of data regarding its long-term behavior and durability, especially in Brazil. To anticipate these results, the application of accelerated degradation protocols combined with mechanical tests allows for a better understanding of the mechanical behavior and durability of the material in exposure environments over predefined periods. The objective of this study was to evaluate the durability of full-scale concrete beams reinforced with steel and Glass Fiber Reinforced Polymer (GFRP) bars using the accelerated conditioning protocols of ACI 440.9R (2015). The experimental program initiated by Mazzú (2020) was completed, exposing reinforced concrete beams to laboratory conditions and saline solution for 1000, 5000, and 10000 hours. Three-point bending tests were conducted to assess the mechanical behavior and durability after the complete accelerated degradation cycle. An additional experimental program was carried out in which GFRP bars, both unprotected and protected by concrete, were subjected to the same conditions as the beams and evaluated through mechanical and microstructural tests to investigate their durability and degradation mechanisms. After 5000 hours of saline immersion, the GFRP-reinforced beams showed a 12% reduction in load capacity and a 13% reduction in stiffness, demonstrating the efficiency of the applied protocol in accelerating degradation. GFRP bars protected by concrete showed greater reduction in tensile strength after 10000 hours of exposure compared to unprotected GFRP bars (62.99% and 47.85%, respectively), due to the influence of concrete alkalinity. However, the degradation mechanism was the same for both conditions, mainly based on polymer matrix hydrolysis.
Experimental analysis of the behavior and durability of concrete beams reinforced in flexure with GFRP bars subjected to saline solution exposure
Keywords: Concreto; GFRP; Durabilidade; Acondicionamento acelerado; Degradação; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL::MATERIAIS E COMPONENTES DE CONSTRUCAO